Walking through deprived neighbourhoods: Meanings and constructions behind the attributes of the built environment. (July 2019) - Figueroa Martínez, Cristhian; Hodgson, Frances; Mullen, Caroline; Timms, Paul
Highlights: Provides an analysis of the relationship between the built environment and walking. Analyses deprived neighbourhoods using walking interviews, mapping and observation. Suggests that the relevant aspects of the built environment are those signified. Reveals that the built environment can induce slight and profound changes on walking. Abstract: Existing research on relations between the built environment and walking has mostly focused on people's propensity to walk through a given area. Little work has investigated how people's experience of walking is mediated by their reading of how elements of the built environment confer social indications such as safety or threat, territoriality or community. Still less research has focused on walking through deprived areas. The research reported here begins to redress this absence by exploring how and why aspects of the built environment influence the experience of walking by those who live in disadvantaged neighbourhoods of Santiago de Chile. Mixed qualitative methods, including mobile interviews with residents, researcher observation and mapping were used to explore experiences of walking in three housing estates in Santiago. The findings reveal that residents' perceptions of safety or danger are shaped by the presence of deterioration of buildings and public space, territorial demarcations, the features of the borders of public space and the urban form. Those features are used to identify risks, are signified through personal experiences, knowledge and social constructions and induce changes on pedestrian trips that can be slight, by altering attitudes towards certain places, or profound, by involving adjustments on everyday routes.